1998
DOI: 10.1046/j.1440-1614.1998.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of comorbid anxiety in schizophrenia, schizoaffective disorder and bipolar disorder

Abstract: Almost none of those with anxiety disorders were being treated for them, primarily because the severity of the acute psychotic illness required full diagnostic and therapeutic attention. Patients were generally discharged as soon as their psychotic episode was resolved, with little recognition of the presence of an anxiety disorder. Given that anxiety disorders are relatively responsive to treatment, greater awareness of their comorbidity with psychosis should yield worthwhile clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 18 publications
6
109
3
1
Order By: Relevance
“…Other studies of anxiety disorder in schizophrenia reported a higher anxiety rate of 43% 23 and 41.5% 22 . These higher rates may be explained by the use of in-patients who may report higher rates of anxiety than the out-patients 23 and the measurement of lifetime rates instead of current rate of anxiety disorder 11 .…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Other studies of anxiety disorder in schizophrenia reported a higher anxiety rate of 43% 23 and 41.5% 22 . These higher rates may be explained by the use of in-patients who may report higher rates of anxiety than the out-patients 23 and the measurement of lifetime rates instead of current rate of anxiety disorder 11 .…”
mentioning
confidence: 79%
“…A study done in Australia on 100 consecutively admitted in-patients with schizophrenia found that anxiety disorders though common (45% in the patients studied), was unrecognized by clinicians in almost all of the patients 23 . Craig, Hwang and Bromet reported that only about 10 percent of patients with co-morbid obsessive compulsive symptoms were identified by the clinicians.…”
mentioning
confidence: 97%
“…Three populationbased studies conducted in Italy and USA, reported lifetime prevalence rates of comorbid OCD in BD patients ranging between 11.1% and 21% (3,23,24). In hospital-based studies, the lifetime prevalence of comorbid OCD in BD patients ranged between 1.8% and 35.1% (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) depending on the features of the BD study population included (schizoaffective disorder, bipolar type). When restricting the analysis to studies with sample size greater than 250, the OCD-BD prevalence range was narrower (3-13.6%) (24,26,27,31,38,39), and the mean prevalence rate of BD-I comorbidity was 15%, while BD-II was 12.6% (24,38,39).…”
Section: Included Studiesmentioning
confidence: 99%
“…Social anxiety is among the most prevalent and debilitating affective disturbances manifest in people with psychosis with rates ranging between 8% to 36% (1,2,3,4,5,6,7,8). Social anxiety is usually accompanied by high levels of depression and exerts a significant impact on social disability (2,5,7,8,9).…”
Section: Introductionmentioning
confidence: 99%